2021
DOI: 10.1039/d1ce00226k
|View full text |Cite
|
Sign up to set email alerts
|

Deep-ultraviolet transparent alkali metal–rare earth metal sulfate NaY(SO4)2·H2O as a nonlinear optical crystal: synthesis and characterization

Abstract: A new alkali metal-rare earth metal sulfate with the formula NaY(SO4)2.H2O has been synthesized using a mild hydrothermal method. It crystallizes in the noncentrosymmetric trigonal space group P3121 (No. 152)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…A Tb atom is connected to eight O atoms to form a [TbO 8 ] polyhedron, where the Tb–O bond lengths are in the range of 2.2767–2.5562 Å (Figure b), which is consistent with the results reported in the previous literature, indicating their rationality. An S atom is linked to four O atoms to form a [SO 4 ] tetrahedra with the S–O bond lengths of 1.426(6)–1.496(6) Å and the O–S–O bond angles of 109.3(4)–114.0(4)° (Figure c), which is also reasonable and confirmed by previous papers. ,, It can be noted that the O in [TbO 8 ] comes from 7 [SO 4 ], and 2 of them come from the same [SO 4 ] (Figure a). With S as the center, the bonding situation among K, Tb, S, and O atoms can be clearly observed; one [SO 4 ] group is neighbored to four Tb atoms and two K atoms through O atom (Figure b).…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…A Tb atom is connected to eight O atoms to form a [TbO 8 ] polyhedron, where the Tb–O bond lengths are in the range of 2.2767–2.5562 Å (Figure b), which is consistent with the results reported in the previous literature, indicating their rationality. An S atom is linked to four O atoms to form a [SO 4 ] tetrahedra with the S–O bond lengths of 1.426(6)–1.496(6) Å and the O–S–O bond angles of 109.3(4)–114.0(4)° (Figure c), which is also reasonable and confirmed by previous papers. ,, It can be noted that the O in [TbO 8 ] comes from 7 [SO 4 ], and 2 of them come from the same [SO 4 ] (Figure a). With S as the center, the bonding situation among K, Tb, S, and O atoms can be clearly observed; one [SO 4 ] group is neighbored to four Tb atoms and two K atoms through O atom (Figure b).…”
Section: Resultssupporting
confidence: 87%
“…Crystal structure analysis showed that it crystallized in the orthorhombic space group P2 1 2 1 2 1 with cell parameters a = 5.43950 (10) 1c), which is also reasonable and confirmed by previous papers. 37,38,51 It can be noted that the O in [TbO 8 ] comes from 7 [SO 4 ], and 2 of them come from the same [SO 4 ] (Figure 2a). With S as the center, the bonding situation among K, Tb, S, and O atoms can be clearly observed; one [SO 4 ] group is neighbored to four Tb atoms and two K atoms through O atom (Figure 2b).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Traditionally, the search of nonlinear optical (NLO) materials focused on borate systems [22], on the other hand, several NLO sulfate crystals were synthesized in recent years [23][24][25][26][27]. As to the Re 2 O 2 SO 4 oxysulfates, the crystal structure of Nd 2 O 2 SO 4 [28] was solved in the non-centrosymmetric (I222) space group and thus this class of compounds can be a candidate for NLO materials.…”
Section: Introductionmentioning
confidence: 99%